2018
DOI: 10.1016/j.chemosphere.2018.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Seabird colonies as relevant sources of pollutants in Antarctic ecosystems: Part 1 - Trace elements

Abstract: Global distillation is classically pointed as the biggest responsible for contaminant inputs in Polar ecosystems. Mercury (Hg) and other trace elements (TEs) also present natural sources, whereas the biologically mediated input is typically ignored. However, bioaccumulation and biomagnification combined with the fact that seabirds gather in large numbers into large colonies and excrete on land might represent an important local TEs input. A previous work suggested these colonies as sources of not only nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 79 publications
8
31
2
Order By: Relevance
“…Some studies (e.g. Roosens et al 2007;Choy et al 2010), including recent ones by the authors of the present work (Cipro et al 2018a(Cipro et al , 2019, confirmed the role of seabird colonies in Antarctic ecosystems as relevant secondary sources of POPs and TEs as well.…”
Section: -Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Some studies (e.g. Roosens et al 2007;Choy et al 2010), including recent ones by the authors of the present work (Cipro et al 2018a(Cipro et al , 2019, confirmed the role of seabird colonies in Antarctic ecosystems as relevant secondary sources of POPs and TEs as well.…”
Section: -Introductionsupporting
confidence: 81%
“…A subset of the samples is taken from previous works of the authors (Cipro et al 2018a(Cipro et al , 2019, i.e., the samples from the austral summers of 2013-14 and 2014-15. To those, a new subset has been added, with samples collected in 2017-18 (n=3 for algae, 22 for lichen, 21 for moss, 10 for soil), always in locations comprised within the previous dataset.…”
Section: -Materials and Methods 21 -Samplingmentioning
confidence: 99%
See 3 more Smart Citations